Biotechnological production of polyhydroxyalkanoates from glycerol: A review - Koller, Martin; Obruča, Stanislav (Elsevier, 2022)
Current worldwide threats related to global warming, climate change, and depletion of limited fossil resources necessitate the switch of industry towards producing carbon-neutral chemicals, solvents, fuels, and plastics. In this context, biotechnology offers alternatives to established plastics from petrochemistry, namely microbial polyhydroxyalkanoate (PHA) biopolyesters. PHA, circular in their nature, span a broad range of material properties, which can be finetuned by the biotechnological production strategy; this way, PHA can mimic both thermoplastics and elastomers from petrochemistry. However, it's the still high production costs that impede the ultimate market penetration of PHA to replace established recalcitrant types of plastics. Selecting inexpensive waste and surplus materials from diverse industrial sectors for being used as biotechnological feedstocks for the production of PHA is among the most auspicious steps to increase PHA's competitiveness with petrochemical plastics. In this context, glycerol, an abundant carbonaceous side stream from steadily increasing biodiesel production, is among the globally emerging inexpensive materials for this purpose. The review article at hand provides an overview of how the renewable, high-volume, low-value resource glycerol can be converted by most diverse prokaryotic production strains to PHA of different structure and properties and highlights obstacles and particular benefits when using this waste stream for biopolyesters synthesis, with special emphasis dedicated to most recent developments, and the application of naturally occurring organisms (wild type strains) isolated from most diverse habitats.

Current worldwide threats related to global warming, climate change, and depletion of limited fossil resources necessitate the switch of industry towards producing carbon-neutral chemicals, solvents, fuels, and plastics. In this context, biotechnology offers alternatives to established plastics from petrochemistry, namely microbial polyhydroxyalkanoate (PHA) biopolyesters. PHA, circular in their nature, span a broad range of material properties, which can be finetuned by the biotechnological production strategy; this way, PHA can mimic both thermoplastics and elastomers from petrochemistry. However, it's the still high production costs that impede the ultimate market penetration of PHA to replace established recalcitrant types of plastics. Selecting inexpensive waste and surplus materials from diverse industrial sectors for being used as biotechnological feedstocks for the production of PHA is among the most auspicious steps to increase PHA's competitiveness with petrochemical plastics. In this context, glycerol, an abundant carbonaceous side stream from steadily increasing biodiesel production, is among the globally emerging inexpensive materials for this purpose. The review article at hand provides an overview of how the renewable, high-volume, low-value resource glycerol can be converted by most diverse prokaryotic production strains to PHA of different structure and properties and highlights obstacles and particular benefits when using this waste stream for biopolyesters synthesis, with special emphasis dedicated to most recent developments, and the application of naturally occurring organisms (wild type strains) isolated from most diverse habitats.
Biotechnological production of polyhydroxyalkanoates from glycerol: A review
Keywords: necator DSM 545; Cupriavidus-necator; poly(3-hydroxybutyrate) production; Pseudomonas-putida; Ralstonia-eutropha; crude glycerol; waste glycerol; transcriptome analysis; biodiesel production; agricultural waste; necator DSM 545; Cupriavidus-necator; poly(3-hydroxybutyrate) production; Pseudomonas-putida; Ralstonia-eutropha; crude glycerol; waste glycerol; transcriptome analysis; biodiesel production; agricultural waste